2000
DOI: 10.1029/2000jd900068
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐atmosphere nitrogen oxide fluxes: Effects of root disturbance

Abstract: Abstract. Chambers are the most common method used to sample soil-atmosphere fluxes of trace gases. Working in tree plantations in Costa Rica and in subtropical forest in Puerto Rico, we performed controlled experiments in order to evaluate whether installation of the chamber bases into the soil affects the soil-atmosphere flux of nitrogen oxides. Installation of chambers severed roots. We found a short-term disturbance effect related to chamber installation. Fluxes of nitrogen oxides increased by as much as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…2.2) other possible sources of errors need to be discussed. Keller et al (2000) investigated the effect of soil disturbance by installation of measuring chambers. For tropical soils a possible stimulation of nitrogen oxide emissions over a time period up to one month was reported and interpreted to be caused by cutting of roots during installation of measuring chambers.…”
Section: Discussionmentioning
confidence: 99%
“…2.2) other possible sources of errors need to be discussed. Keller et al (2000) investigated the effect of soil disturbance by installation of measuring chambers. For tropical soils a possible stimulation of nitrogen oxide emissions over a time period up to one month was reported and interpreted to be caused by cutting of roots during installation of measuring chambers.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Matson et al [1990] found that N 2 O fluxes measured from permanently installed chamber bases showed significant increases compared to fluxes from control bases emplaced immediately before measurement after only 5 hours of insertion of the first set of bases. In Costa Rica and Puerto Rico, Keller et al [2000] observed increased fluxes of NO and N 2 O from several hours up to 6 weeks after base emplacement.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies in tropical forests soils in Brazil, Costa Rica, and Puerto Rico suggested that root mortality increases emissions of NO and N 2 O from the soil surface [ Matson et al , 1990; Keller et al , 2000]. In these studies, the effect of root mortality was inferred from observations of increased trace gas emissions following the emplacement of bases for soil enclosures to depths of 1 to 2 cm into the soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of sampling, a cylindrical chamber 18 cm tall and 15 cm diameter was placed on each of the collars and a large rubber band of 10 cm diameter and 5 cm width was used to seal the chamber. The collar installation in the v www.esajournals.org soil affects the lateral gas diffusivity in the soil under the chamber Livingston 2001, Rochette andEriksen-Hamel 2008), can create preferential water and gas pathways through the crevasse between the soil matrix and the chamber wall and can disturb root growth (Keller et al 2000, Varner et al 2003, Rochette and Eriksen-Hamel 2008. All these changes can lead to biased measurements of net gas flux.…”
Section: Soil N 2 O and Ch 4 Emissionsmentioning
confidence: 99%